Depression, Anxiety, and Stress in Adolescents Using the Etonogestrel Implant: A Prospective Cohort Study. - Freita, Gabriela Silva [UNESP]; Rota, Sara Ribeiro [UNESP]; Schmitt, Juliano Vilaverde [UNESP]; Dias, Flávia Neves Bueloni [UNESP]; Dias, Daniel Spadotto [UNESP]; Poloni, Priscila Ferreira [UNESP]; Nahas, Eliana Aguiar Petri [UNESP]; Schmitt, Eneida Maria Boteon [UNESP] (Elsevier, 2025)
OBJECTIVE: This study evaluated changes in symptoms of depression, anxiety, and stress among adolescents using the etonogestrel subdermal implant. It analyzed psychometric score variations and the proportion of participants with values above normative thresholds to assess the method's safety with respect to mood symptoms. STUDY DESIGN: Prospective cohort study involving female adolescents aged 12-19 years who chose the etonogestrel subdermal implant for contraception. Participants completed the Depression, Anxiety, and Stress Scale for Adolescents (EDAE-A) at baseline, and at three and six months post-insertion. We performed statistical analyses using the Friedman test, chi-square tests, and relative risk estimates. Subgroup analyses were conducted for participants with elevated baseline scores. Significance was set at p ≤ 0.05. RESULTS: Of the 97 participants enrolled, 66 completed all follow-up stages. The median age was 17 years. Baseline EDAE-A scores indicated mild symptoms of depression and anxiety and normal stress levels. Approximately 50% of participants scored above normative thresholds across all time points, but scores remained stable over six months, with no statistically significant changes in any domain. Among adolescents with elevated baseline symptoms, we observed a trend toward reduced depressive symptoms (p = 0.06). Prior hormonal contraceptive use did not significantly influence scores. CONCLUSIONS: Use of the etonogestrel implant was not associated with significant changes in depression, anxiety, or stress symptoms among adolescents over six months. The findings support the psychological safety of the method and suggest that mood symptoms are more common in this population and are more likely related to developmental factors than to contraceptive use.